Immediate implant in the esthetic zone: An evidence-based clinical guide - Mansour K Assery (Wolters Kluwer Medknow Publications, 2014)
Immediate implant placement in the esthetic zone is a topic that has recently received a lot of attention in the literature. Successful implant placement at the time of extraction in the esthetic zone is a challenge, requiring management of soft-tissue, atraumatic extraction placement of the implant and later the prosthetic stage. This article looks reviews recent literature on the topic of immediate implant placement in the esthetic zone and the clinical steps involved. The article also looks at recent evidence on patient satisfaction and discusses the merits, demerits of such a procedure and precautions to be taken by the practitioner to minimize failure.